STIGMA DUNIA MIXOLOGY DI MASYARAKAT KOTA BATAM - Novi; Mikasari, Dewi Aurora (JURNAL MENATA, 2022)
Globalization that has accompanied daily activities does have a significant influence on Batam people’s opinion about the world of mixology from a scientific point of view, it even tends to lead to negative opinions and stereotypes on people who are involved in mixology activities. The researcher used an approach by using descriptive qualitative method to collect data information by using non-participant observation, semi-structured interviews and documentation technique. The results shows that the factor that caused stigma in mixology’s world usually because of religion, culture, and people behavior that is supported by environment and knowledge. Religion and culture factors and environtment also influence stigma to be born and stay until now because of dominant east culture in Batam city that is not identic with alcohol or even mixology’s world.